193 times hope this helps
Answer:
Triangle rsu = Triangle tus
Statements Reasons
UR ≅ TS Definition of Rectangle
US ≅ US Reflexive Property
<U, <T, <R, <S are all congruent and right angles
Definition of Rectangle
ΔRSU ≅ ΔTUS Side, Angle, Side
UR ≅ TS CPCTC
Just draw a reverse angle,hence you get comparison.
So, satisfying S-S-S
RUS ≅ SUT
RSU ≅ TUS
So, angle
URS = angle TUS
2. Pythagoras Theorem
Triangle RUS
A^2 + B^2 = C^2
Uu^2 + Ss^2 = Rr^2
√Rr = Rr^2 = x
Triangle TUS
A^2 + B^2 = C^2
Ss^2 + Uu^2 = Tt^2
√Tt = Tt^2 = x
UR measure / sin (60) x (90) = US measure.
ST measure / sin (60) x (90) = US measure.
Proves angles RSU = 30 degree
Proves angles TUS = 30 degree
As all adjacent angles in a triangle add up to 180 degree.
Answer:
See below
Step-by-step explanation:
13x + 5 + 17x - 4.5 + x
NOTE: You can only add/subtract LIKE terms . Here we have variable terms in x (13x , 17x and x) and 2 constants ( 5 and 4.5).
Sarah's next line is
18x + 17x - 4.5 + x
This is incorrect . It looks like she added 13x + 5 and got 18x!! Which is of course wrong because they are NOT LIKE terms. 5 is a constant and 13x is a variable term in x.
The third line is correct:-
35x - 4.5 + x.
She has added the 2 variables 17x and 18x.
Fourth line is 30.5x + x. She's at it again - Trying to subtract 4.5 from 35x .
Last line 31.5x
She has added the 2 terms in x correctly, but the final answer is wrong of course due to the earlier errors.
Answer:
2y+15
Step-by-step explanation:
y+(15+y)
y+15+y
(y+y)+15
2y+15
<h2>
Answer: x = 6</h2>
* = things that have changed or are being changed
<h2>
Explanation:</h2>
1. rearrange terms
*4
4 + 3
* = 5
+ 2
+ 2
0
*3x + 44* = 5x + 2 + 20
2. combine like terms
3 + 44 = *5x + 2* + 20
3 + 44 = *7x* + 20
3. Subtract 4
4 from both sides of the equation
3x + 44 = 7x + 20
3x + 44 *-44* = 7x + 20 *-44*
4. Simplify
(Subtract the numbers)
3x + *44 - 44* = 7x + 20 - 44
3x = 7x + 20 - 44
(Again)
3x = 7x + 20 *- 44*
3x = 7x - 24
5. Subtract 7
from both sides of the equation
3x = 7x - 24
3x *- 7x* = 7x - 24 *- 7x*
6. Combine like terms
*3x - 7x* = 7x - 24 - 7x
*-4x* = 7x - 24 - 7x
(Again)
-4x = *7x* - 24 *- 7x*
-4x = - 24
7. Divide both sides of the equation by the same term
-4x = - 24

8. Simplify
(Cancel terms that are in both the numerator and denominator)

*x* = 
(Divide the numbers)
x = 
x = 6